The possible potential therapeutic targets for drug induced gingival overgrowth - Subramani, Tamilselvan; Rathnavelu, Vidhya; Mohammed Alitheen, Noorjahan Banu (Hindawi Publishing Corporation, 2013)
Gingival overgrowth is a side effect of certain medications. The most fibrotic drug-induced lesions develop in response to therapy with phenytoin, the least fibrotic lesions are caused by cyclosporin A, and the intermediate fibrosis occurs in nifedipine-induced gingival overgrowth. Fibrosis is one of the largest groups of diseases for which there is no therapy but is believed to occur because of a persistent tissue repair program. During connective tissue repair, activated gingival fibroblasts synthesize and remodel newly created extracellular matrix. Proteins such as transforming growth factor (TGF), endothelin-1 (ET-1), angiotensin II (Ang II), connective tissue growth factor (CCN2/CTGF), insulin-like growth factor (IGF), and platelet-derived growth factor (PDGF) appear to act in a network that contributes to the development of gingival fibrosis. Since inflammation is the prerequisite for gingival overgrowth, mast cells and its protease enzymes also play a vital role in the pathogenesis of gingival fibrosis. Drugs targeting these proteins are currently under consideration as antifibrotic treatments. This review summarizes recent observations concerning the contribution of TGF-β, CTGF, IGF, PDGF, ET-1, Ang II, and mast cell chymase and tryptase enzymes to fibroblast activation in gingival fibrosis and the potential utility of agents blocking these proteins in affecting the outcome of drug-induced gingival overgrowth.